Adipose Mitochondrial Respiratory Capacity in Obesity is Impaired Independently of Glycemic Status of Tissue Donors. Issue 5 (26th March 2019) - Wessels, Britta; Honecker, Julius; Schöttl, Theresa; Stecher, Lynne; Klingenspor, Martin; Hauner, Hans; Skurk, Thomas
Abstract : Objective: The study aimed to investigate how obesity and glycemic state affect mitochondrial respiration and ATP–generating pathways in mature human adipocytes. Methods: Subcutaneous (sc) and visceral (vc) adipocytes were isolated from patients undergoing abdominal surgery. Respiratory chain function was analyzed by high‐resolution respirometry. Adipocyte ATP levels and lactate release were measured separately in the presence of either glycolysis (2‐deoxy‐D‐glucose) or ATP synthase (oligomycin) inhibitors. Results: A significant negative correlation between oxidative phosphorylation capacity and the BMI of tissue donors found in sc adipocytes ( P < 0.05). Furthermore, respirometry revealed an inverse relationship between BMI and the electron transfer system capacity of sc ( P < 0.05) but not vc adipocytes. In both depots, the respiratory capacity was not affected by the glycemic state. A positive correlation between BMI and adipocyte lactate release was measured independently of the tissue origin (sc: P = 0.01; vc: P < 0.05). Direct ATP measurements indicated that energy demands of adipocytes were predominantly fulfilled by glycolytic activity. Conclusions: The study's data suggest that obesity is the primary driver of impaired adipocyte mitochondrial respiration because the glycemic state did not further deteriorate this situation. The adipocytes' energy needs are covered primarily by the glycolytic pathway.